PERAN KARAKTERISTIK INDIVIDU AUDITOR PADA PENENTUAN TINGKAT MATERIALITAS - Sekar Mayangsari (PT. Cendekia Sapta Indonesia, 2023)
This study aims to analyze and provide empirical evidence on the influence of professionalism, professional ethics, gender, and self-Efficacy to consider the level of materiality with the locus of control as moderation. Consideration of materiality level of professionalism conducted by the auditor is measured by, professional ethics, gender, and self Efficacy and locus of control as moderation. The data used in this study contains the perceptions of independent auditors who fill out the questionnaire. The sample in this study involves an independent auditor at Public Accounting Firm in Jakarta Region. Questionnaires were distributed as many as 150 questionnaires. Data collection techniques in this study is data collection techniques through survey techniques by distributing questionnaires directly to the respondent concerned, with the aim of obtaining a representative sample in accordance with predetermined criteria. By using multiple regression, this study show that professionalism affects the consideration of materiality level, while professional ethics, gender, and self Efficacy have no effect on the materiality level. The other result show that the locus of control strengthen the influence of professionalism, ethics, gender and self efficacy on the consideration of the level of materiality. Keyword: Professionalism, professional ethics, gender, self efficacy, materiality level, and locus of control